2021
DOI: 10.3389/fped.2021.779663
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Procalcitonin to Detect Early-Onset Sepsis in Newborns: A Promising Biomarker

Abstract: Background: Up to 7% of neonates born in high-income countries receive antibiotics for suspected early-onset sepsis (EOS). Culture-proven neonatal sepsis has a prevalence of 0.2%, suggesting considerable overtreatment. We studied the diagnostic accuracy of umbilical cord blood and infant blood procalcitonin (PCT) in diagnosing EOS to improve antibiotic stewardship.Methods: Umbilical cord blood PCT was tested in newborns ≥ 32 weeks of gestation. Groups were defined as following: A) culture-proven or probable EO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In the present study, PCT levels in the infected group were statistically higher (1.5±0.9 ng/dl) than in the uninfected group (1.1±0.8 ng/dl) p=0.042. This was in accordance with another study (15). Furthermore, others found that PCT concentrations > 0.5 g/L were linked to a greater incidence of EOS (OR 2.18; CI95% 1.58-3.02; p < 0.0001) (16).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, PCT levels in the infected group were statistically higher (1.5±0.9 ng/dl) than in the uninfected group (1.1±0.8 ng/dl) p=0.042. This was in accordance with another study (15). Furthermore, others found that PCT concentrations > 0.5 g/L were linked to a greater incidence of EOS (OR 2.18; CI95% 1.58-3.02; p < 0.0001) (16).…”
Section: Discussionsupporting
confidence: 91%
“…A monocenter retrospective study of 2151 newborns con rmed the ability of cord blood PCT to detect early neonatal infection (cut-off value, 0.6 ng/ml; AUC, 0.96; sensitivity, 0.92; speci city, 0.97) [19]. Besides, in a prospective, single-center, case-control study, a cord blood PCT cut-off value of 0.1 ng/ml in newborns ≥ 32 weeks corresponded with an AUC of 0.8, sensitivity of 0.83 and speci city of 0.62 [20]. Furthermore, Lautridou et al [21] found that elevated umbilical cord PCT was an independent risk factor for mortality in preterm infants with GA < 33 weeks.…”
Section: Discussionmentioning
confidence: 80%
“…reported a low umbilical cord blood procalcitonin in the healthy controls and newborn infants who were not eligible for antibiotic therapy corresponding with their non-infectious state. 27 In contrast, the sensitivity and the positive predictive value seem to be less powerful, which does not allow its use as a positive diagnostic tool. 15 Two biomarkers of inflammation appear to be of interest for the diagnosis of EOS: interleukin-6 (IL-6)…”
Section: Discussionmentioning
confidence: 99%